100 things to know about science - Frith, Alex; Lacey, Minna; Martin, Jerome; Melmoth, Jonathan (London Usborne, 2015)
Science is a huge topic, but this friendly book breaks it down into bite-sized chunks, making it an accessible introduction for anyone who wants to find out about this fascinating subject. Highly illustrated, in a pictorial, 'infographics' style, with snippets of information about all aspects of science from particle physics to genes and DNA.
Q
b
b